(untitled) (Community Based Medical Journal, 2022)
Lightning is one of the leading causes of weather-related fatalities. A man, approximately 30 years old, was brought to the morgue of Kishoreganj District Hospital, Bangladesh, in July 2021, known to be lightning strike victim. During postmortem examination, various types of skin burns were found in the body, at an entry site on and near the head, and at an inferiorly located exit site. The skin injuries consisted of superficial burns, charring, and singed hair; however, there was no deep burn. „Lichtenberg figures‟ were found. Internal findings at autopsy were nonspecific. Epidemiologically, the total number of global annual lightning fatalities range from 6,000 to 24,000 per year. In recent years, Bangladesh experiences a high rate of lightning deaths. We feel that the number of deaths by lightning should be seen as a call to action. Hence, deaths by lightning should be regarded as a public health problem in the country and necessary measures must be taken. Our case study aims to draw the attention of the physicians and public health department on injuries and deaths due to lightning strike. It is also important for forensic professionals to be familiar with the nature of injuries caused by lightning and lightning strike deaths. CBMJ 2022 January: vol. 11 no. 01 P: 52-55